Prevention of β-amyloid-induced toxicity in a differentiated neuronal (IMR32) cell line by Khaya grandifololia (Welw) C. DC. - Ella Fils Armand; Manjula Shantaram; Simon Ngamli Fewou; Frédéric Nico Njayou; Sayali Chandrashekhar Deolankar; Prashant Kumar Modi; Paul Fewou Moundipa (International Journal of Phytomedicine, 2020)
Alzheimer’s disease (AD) belongs to the class of neurodegenerative disorder and is biochemically characterized by amyloid-β (Aβ) plaques deposition, accumulation of neurofibrillary tangles (NFTs) accumulation and ultimately neuronal loss. Even though, the progress made in developing efficient AD therapy, there is no effective drug capable to stop and/or slow down AD progression. In the current article, we investigated the neuroprotective effect of Khaya grandifololia crude extract and fraction 2 against Aβ42-induced cytotoxicity and hyperphosphorylation of tau protein in differentiated neuronal cells (IMR32). Reactive oxygen species production, apoptosis and mitochondrial dynamics and function, synaptic protein, and tau phosphorylation were evaluated using fluorescence microscopy and immunoblotting. Cell viability was assessed using the MTT assay. Findings revealed that exposure of differentiated IMR32 cells to Aβ42 alone induced the impairment of mitochondrial dynamics, decrease synaptic protein expression and increase hyperphosphorylation of tau protein (phospho tau181). In contrast, the presence of crude extract and KGf2 significantly inhibited the cleavage of Caspase-3 activation. In addition, the levels of synaptic proteins (Symptosomal associated protein 25 and Synaptosin) and superoxide dismutase were restored upon treatment with crude extract and fraction 2. Hyperphosphorylation of tau protein (Thr181) and ERK (Thr202/Tyr205) activities were also significantly reduced after treatment with crude extract and fraction 2. Our findings suggest that KG extract is a potential source for candidate drug against AD and may contribute to the development of efficient therapeutic strategy against AD.